Pengaruh Pemberian Charcoal Tulang Ikan Kambing-kambing (Abalistes stellaris) pada Pakan untuk Mereduksi Kadar Amonia pada Media Budidaya. - Aurelia Reta; Azwar Thaib; Nurhayati nurhayati (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
Water quality is one of the most important factors in fish cultivation. Water quality is influenced by both physical and chemical factors. These factors include temperature, DO, PH, ammonia, nitrate, and nitrite. Charcoal in particular is a solid material that has pores to absorb ammonia, nitrogen and also remove poison and grimes in cultivation media. Charcoal has solid pores which contain 85-95% carbon produced by substances that heated in a furnace for around 2 hours with 600ºC temperature. This research aims to determine the effect of bonefish charcoal distribution in reducing the ammonia level towards Nile Tilapia’s (Oreochromis niloticus) growth and life sustainability. This research used descriptive analysis. There were 4 treatments done in this study: treatment A (0%), treatment B (1%), treatment C (2%), and treatment D (3%). The result showed that adding bonefish charcoal to the fish feed proved to be effective in reducing the ammonia level in cultivation media. The best result was found in treatment D (3%) valued 0,15 mg/l, followed by treatment B (1%) with 0,24 mg/l, treatment A (control) 40 mg/l, and treatment C (2%) with 0,51 mg/l.